Inklusion und Transformation in Organisationen - König, Oliver (Verlag Julius Klinkhardt, 2022)
Transformation, in contrast to "change," represents a move away from merely optimizing existing structures. Rather, it is about thinking about and shaping inclusive and sustainable communities as projects for the future. Although organizations play a decisive role in structuring and standardizing people's lives and thus also have a decisive impact on their opportunities for participation, research on inclusion has so far only touched on questions of the mutual influence of inclusion and organization. This anthology opens up theoretical perspectives on questions of how inclusion is handled and processed, and provides insight into practical examples of "making organizations different". In doing so, this book uses the model of the Three Horizons to show that people are capable of developing an awareness of the future and are thus fundamentally capable of changing patterns.